Analiza medijske koncentracije i scene u republici Makedoniji - Donev, Dejan (NVO Civilni forum Nikšić, 2013)
Poor a working situation and undifferentiated structure of the media and journalism allows for media workers and journalists more freedom and creativity that they should justify a higher degree of quality culture in his profession, in which the central place has developed a media ethics, deepened and terminology and distinct from the subject of journalistic ethics, and ethics of the public, and thus a higher degree of professionalism, free from economic and political influences. But the reality is very much different – the absence of critical approaches to media content, pressure and fear of one’s own existence contributed to the journalists often samocenzurišu in the interest of keeping their job positions. At the same time, plural media sphere and the creation of market relations and competition, are not automatically contribute to increasing the degree of freedom of expression, articulation and critical public participation of citizens in the political process. Previous contributions to the media scene is constantly exposed to shock, not only criticism from the European Union, but also from other relevant institutions and activists. The media and the journalistic profession are under persistent pressure from political and economic elites, which speaks to media ownership, economic pressures, lack of respect for professional standards and lack of ethics, seem to be the dominant issues in relation to the media situation in the Republic of Macedonia.
Analysis of Media Concentration and scenes in the Republic of Macedonia
Keywords: professionalism, ethics in journalism, media landscape, media ownership, freedom of speech